2015
DOI: 10.3906/tar-1406-153
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of some Apiaceae plants commonly used inherby cheese in Eastern Anatolia

Abstract: Traditional uses of wild edible plants in daily diets are common in Eastern Anatolia. It is well known that more than 40 different plant species have been used as fresh vegetable, dried herbs, and pickled plants in some sole or mixed milk and meat products. The major use of wild edible plants is Van herby cheese in this region. To date, the mineral compositions of wild edible plants used in Van herby cheese production have been studied individually. In the present study, the plants were grouped by their plant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
52
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 14 publications
8
52
3
Order By: Relevance
“…; Kagale and Sabale ; Kalita et al . ; Tuncturk and Ozgokce ). However, the ash content of the wild plants examined was considerably higher than those of commercial vegetables (0.4–2.0%) (Roe et al .…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…; Kagale and Sabale ; Kalita et al . ; Tuncturk and Ozgokce ). However, the ash content of the wild plants examined was considerably higher than those of commercial vegetables (0.4–2.0%) (Roe et al .…”
Section: Resultsmentioning
confidence: 97%
“…; Turan et al . ; Tuncturk and Ozgokce ). However, our results were very similar to the values of Coruh et al .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…When we evaluate the amount of ash in our samples on DW, it is seen that our study is a little higher than these results. Tunçturk et al 11 50 value was found between 0.24-3.33 mg/ml on DW. Taskin and Bitis 14 evaluated the total phenolic contents and antioxidant activity of ethanol extracts from eight wild edible plants in Turkey.…”
Section: Resultsmentioning
confidence: 99%
“…There are a number of scientific works in Turkey and other countries in this topic. 5,6 In this work, some nutritional value and mineral composition of Cephalaria schrader were determined in details. Results obtained from laboratory analysis were compared by previous scientific researches' findings.…”
Section: Introductionmentioning
confidence: 99%